Effect of Abutment Modification and Cement Type on Retention of Cement-Retained Implant Supported Crowns - Farzin, Mitra (J Dent (Tehran), 2014)
OBJECTIVE: Provisional cements are commonly used to facilitate retrievability of cement-retained fixed implant restorations; but compromised abutment preparation may affect the retention of implant-retained crowns.The purpose of this study was to investigate the effect of abutment design and type of luting agent on the retentive strength of cement-retained implant restorations. MATERIALS AND METHOD: Two prefabricated abutments were attached to their corresponding analogs and embedded in an acrylic resin block. The first abutment (control group) was left intact without any modifications. The screw access channel for the first abutment was completely filled with composite resin. In the second abutment, (test group) the axial wall was partially removed to form an abutment with 3 walls. Wax models were made by CAD/CAM. Ten cast copings were fabricated for each abutment. The prepared copings were cemented on the abutments by Temp Bond luting agent under standardized conditions (n=20). The assemblies were stored in 100% humidity for one day at 37°C prior to testing. The cast crown was removed from the abutment using an Instron machine, and the peak removal force was recorded. Coping/abutment specimens were cleaned after testing, and the testing procedure was repeated for Dycal luting agent (n=20). Data were analyzed with two- way ANOVA (α=0.05). RESULTS: There was no significant difference in the mean transformed retention (Ln-R) between intact abutments (4.90±0.37) and the abutments with 3 walls (4.83±0.25) using Dycal luting agent. However, in TempBond group, the mean transformed retention (Ln-R) was significantly lower in the intact abutment (3.9±0.23) compared to the abutment with 3 walls (4.13±0.33, P=0.027). CONCLUSION: The retention of cement-retained implant restoration can be improved by the type of temporary cement used. The retention of cast crowns cemented to implant abutments with TempBond is influenced by the wall removal.